Analysis of Grade XII Students' Mathematical Perceptions in Learning Colligative Properties of Solutions - Aira Putri Januar; Meidiana Dwi Setyo Rini; Nur Feby Richi Ananda; Nur Fikriyah; Puan Afra Edhrinabila; Yurisa Okta Werdiani; Fathiya Rohadatul Aisy; Nina Adriani; Ervinna Ima Suryani Damanik; Safrawita (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Chemistry learning, especially in the subject of colligative properties of solutions, requires quantitative abilities and appropriate mathematical skills. Various studies show that difficulties in mathematics can hinder the understanding of abstract and calculation-based chemistry concepts. However, studies that specifically examine students' perceptions of mathematical ability challenges and their relationship to understanding the colligative properties of solutions are still limited. Therefore, this study aims to describe students' perceptions of mathematical ability and their understanding of the colligative properties of solutions, as well as to analyze the relationship between these two variables. This study uses a quantitative approach with a descriptive-correlational method. The research subjects consisted of 37 students of class XII C6 of State Senior High School 2 Tanjungpinang in the 2025/2026 academic year. Data were collected through a closed questionnaire using a five-point Likert scale consisting of 35 statements, covering the variables of perception of mathematical ability and understanding of the colligative properties of solutions. Data analysis was performed descriptively and using Pearson's correlation test with the help of IBM SPSS Statistics 24. The results showed that students' perceptions of mathematical ability were in the good to fair category, while their understanding of the colligative properties of solutions tended to be in the fair category. The Pearson correlation test produced a coefficient of r = 0.672 with a significance value of 0.000, indicating a strong positive and significant relationship between students' perception of mathematical ability and their understanding of the colligative properties of solutions. These findings emphasize the importance of strengthening students' abilities and confidence in mathematics to improve their understanding of quantitative chemistry concepts.